Electrochromic glass integrated with semitransparent organic solar cell and preparation method of electrochromic glass
By integrating the translucent organic solar cell layer in electrochromic glass and setting up control circuits, the problem of high energy consumption in existing building windows is solved, and intelligent dimming and thermal insulation is achieved, which is suitable for energy-saving and carbon reduction applications of building windows.
Patent Information
- Application Number
- CN202510014674.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-22
AI Technical Summary
Non-energy-efficient glass used in existing building windows results in high energy consumption and lack of high-performance glass that integrates solar cells and electrochromic functions.
An electrochromic glass integrating semi-transparent organic solar cells is developed. By stacking an organic solar cell layer in the electrochromic glass and setting a control circuit to regulate the current direction of the electrochromic layer, intelligent dimming and thermal insulation effects are achieved.
It realizes self-energized electrochromic glass, automatically adjusts transparency according to the light intensity, has good photoelectric conversion and thermal insulation performance, and is suitable for building windows, reducing energy consumption and achieving energy saving and carbon reduction effects.
Smart Images

Figure CN119861516A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of solar cells and electrochromism, and in particular to an electrochromic glass integrated with a semi-transparent organic solar cell and a preparation method thereof. Background Art
[0002] With the rapid development of my country's economy, the scale of construction industry production has continued to expand. In 2021, the total construction area in my country was about 67.7 billion square meters. While the construction industry plays an important role in social development and improvement of people's livelihood, it also brings increasingly serious energy consumption problems. In 2021, my country's building operation energy consumption reached 2.2 trillion kWh, accounting for 21% of China's total social energy consumption. However, since most of the windows in buildings still use non-energy-saving glass, glass energy consumption accounts for a large proportion of building operation energy consumption. For example, in summer, the energy consumed to reduce the room temperature due to solar radiation passing through the glass accounts for 40% to 50% of the total cooling energy consumption. Therefore, the development of relevant energy-saving and carbon-reducing technologies for building window glass is of great significance to achieving the "dual carbon" goal, and it also has broad market and application prospects.
[0003] Organic solar cell technology is an emerging solar cell technology that has developed rapidly in recent years. Its main feature is that the photoelectric active layer is composed of organic semiconductor materials. Compared with traditional opaque silicon-based solar cells, organic solar cell devices have the characteristics of light weight, translucency, intrinsic flexibility and large-area roll-to-roll preparation. They are particularly suitable for integration with architectural window glass: organic solar cells are light in weight, and the weight after integration with architectural window glass mainly comes from glass, which will not significantly increase the transportation and installation costs; the absorption spectrum of organic semiconductors is discontinuous and easy to modulate. If the absorption of the photoelectric active layer of the device is concentrated in the infrared region, infrared light can be converted into electricity and visible light can be transmitted, thereby realizing the functions of power generation, lighting and cooling at the same time. The transmittance of electrochromic devices can change reversibly under the action of an external power supply, and has the functions of lighting regulation and indoor cooling. At present, it has been applied in aircraft windows, car rearview mirrors and buildings. Integrating it with semi-transparent organic solar cells can obtain a new type of energy-saving glass for architectural windows. Therefore, it is of great significance to develop high-performance devices and corresponding integration processes for energy-saving glass for architectural windows based on semi-transparent organic solar cells. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and provide an electrochromic glass with integrated semi-transparent organic solar cells and a preparation method thereof. The electrochromic glass can realize self-power supply and adjust the transparency according to the light intensity, and has good photoelectric conversion performance and heat insulation performance.
[0005] In order to achieve the above-mentioned purpose, the present invention provides an electrochromic glass with integrated semi-transparent organic solar cells, wherein the electrochromic glass comprises an electrochromic layer and an organic solar cell layer stacked thereon, and the organic solar cell layer supplies power to the electrochromic layer; the electrochromic glass is also provided with a control circuit, and the control circuit can change the connection mode between the anode and cathode of the organic solar cell layer and the electrodes of the electrochromic layer to regulate the current direction in the electrochromic layer to achieve coloring or fading.
[0006] A second aspect of the present invention provides a method for preparing the electrochromic glass, which comprises preparing the electrochromic layer and the organic solar cell layer and setting the control circuit to obtain the electrochromic glass.
[0007] The present invention combines a semi-transparent organic solar cell with an electrochromic device and obtains an electrochromic glass with an integrated semi-transparent organic solar cell by setting a specific control circuit. The electrochromic glass can use the semi-transparent organic solar cell to convert the absorbed light energy into electrical energy, which not only reduces the thermal effect of sunlight, but also provides electrical energy for the electrochromic device. At the same time, the control circuit can adjust the direction of the current flowing through the electrochromic device according to the intensity of sunlight, thereby adjusting the transparency of the electrochromic glass. The electrochromic glass of the present invention can realize intelligent dimming, darken when the light is strong to block the strong light, and become transparent when the light is weak to have a high transmittance. The electrochromic glass of the present invention also has excellent heat insulation performance, can achieve the effect of energy saving and carbon reduction, and is suitable for use as a glass window in the field of construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 is a schematic diagram of the specific structure of the electrochromic glass of the present invention;
[0009] Figure 2 It is a schematic diagram of the overall structure of the electrochromic glass of the present invention;
[0010] Figure 3 is a schematic diagram of an electrochromic layer of the electrochromic glass of the present invention;
[0011] Figure 4 This is a schematic diagram of a control circuit for manual regulation of the electrochromic glass of the present invention;
[0012] Figure 5 This is a schematic diagram of a control circuit for automatic regulation of the electrochromic glass of the present invention;
[0013] Figure 6 is an IV curve diagram of the organic solar cell layer of the electrochromic glass prepared in Example 1;
[0014] Figure 7This is a transmission spectrum of the organic solar cell layer of the electrochromic glass prepared in Example 1;
[0015] Figure 8 is a cyclic voltammetry curve of the electrochromic layer of the electrochromic glass prepared in Example 1;
[0016] Fig. 9 is a transmission spectrum diagram of the electrochromic glass prepared in Example 1;
[0017] Fig.10 is an IV curve diagram of the organic solar cell layer of the electrochromic glass prepared in Example 2;
[0018] Fig.11 This is a transmission spectrum of the organic solar cell layer of the electrochromic glass prepared in Example 2;
[0019] Fig.12 is an IV curve diagram of the organic solar cell layer of the electrochromic glass prepared in Example 3;
[0020] Fig.13 This is a transmission spectrum of the organic solar cell layer of the electrochromic glass prepared in Example 3;
[0021] Fig.14 This is a test diagram of the thermal insulation performance of ordinary glass and the electrochromic glass prepared in Example 1. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] In the present invention, each group is independently selected to indicate that when each group appears simultaneously and in multiple places in a compound, they are independently selected and may be the same or different. For example, although The group shown has 4 R7, but these 4 R7 can be selected independently and can be the same or different. In the present invention, The dashed lines in the structures with dashed connecting bonds indicate the connecting sites, which represent the connecting bonds; Formula (1) The solid lines outside the brackets that are not connected to any groups or atoms in the structure with solid line connecting bonds also indicate the connection site and represent the connecting bond. In the present invention, the C group is selected from 1 to 3 formula (2-d) The conjugated structure formed by the alternating positive and negative is shown in the figure. How the conjugated molecules are connected in an alternating positive and negative manner is used as an example: for example, when two formulas (2-d) form a conjugated structure, such as the structural formula The two carbon atoms connected by the dotted line are shared between the two rings to form the structural formula When the three formulas (2-d) are connected, as shown in the structural formula The carbon atoms connected by the dotted lines are shared between the rings to form the structural formula In the present invention, the compound represented by formula (2) is a conjugated macromolecule, which means that the B group, the C group and the The three are conjugated structures with alternating positive and negative polarity. The principle of alternating positive and negative polarity is the same as the principle of forming the conjugated structure of the C group mentioned above. For example, the B group is selected from formula (2-a), the C group is selected from a formula (2-d), the two ends of the B group are connected to one end of the two C groups respectively, one end of the C group is connected to the B group, and the other end is connected to Connected, such as structural As shown, the two carbon atoms connected by the dotted line are shared between the two rings to form the structural formula The structure shown in the formula The general connection shown is the same for other cases and will not be described here.
[0024] On one hand, the present invention provides an electrochromic glass with integrated semi-transparent organic solar cells, wherein the electrochromic glass comprises an electrochromic layer and an organic solar cell layer stacked thereon, and the organic solar cell layer supplies power to the electrochromic layer; the electrochromic glass is also provided with a control circuit, and the control circuit can change the connection mode between the anode and cathode of the organic solar cell layer and the electrodes of the electrochromic layer, so as to regulate the current direction in the electrochromic layer to achieve coloring or fading.
[0025] According to the present invention, preferably, the control circuit is configured as follows: when the intensity of sunlight irradiating the electrochromic glass is high, the voltage provided by the organic solar cell layer causes a forward current to be formed in the electrochromic layer to cause the electrochromic layer to be colored, thereby reducing the transparency of the electrochromic glass; when the intensity of sunlight irradiating the electrochromic glass is weak, the voltage provided by the organic solar cell layer causes a reverse current to be formed in the electrochromic layer to cause the electrochromic layer to fade, thereby increasing the transparency of the electrochromic glass.
[0026] According to the present invention, in order to change the transparency of the electrochromic glass according to the change of the intensity of sunlight, manual control can be achieved through a specific control circuit. Preferably, Figure 4As shown, the control circuit includes a universal conversion switch, which includes eight contacts; the anode of the organic solar cell layer is electrically connected to the first contact 1 and the fifth contact 5, the cathode of the organic solar cell layer is electrically connected to the third contact 3 and the seventh contact 7, the negative electrode of the electrochromic layer is electrically connected to the second contact 2 and the fourth contact 4, and the positive electrode of the electrochromic layer is electrically connected to the sixth contact 6 and the eighth contact 8; thus, when the universal conversion switch connects the first contact 1 and the second contact 2 and the seventh contact 7 and the eighth contact 8, the voltage provided by the organic solar cell layer causes a forward current to be formed in the electrochromic layer to cause the electrochromic layer to be colored, thereby reducing the transparency of the electrochromic glass; when the universal conversion switch connects the third contact 3 and the fourth contact 4 and the fifth contact 5 and the sixth contact 6, the voltage provided by the organic solar cell layer causes a reverse current to be formed in the electrochromic layer to cause the electrochromic layer to fade, thereby increasing the transparency of the electrochromic glass.
[0027] According to the present invention, in order to enable the electrochromic glass to achieve more intelligent automatic dimming according to the change of sunlight intensity, preferably, Figure 5 As shown, the control circuit includes a voltage controller, and the voltage controller includes at least two relays and a single-chip microcomputer, each of the relays includes two contacts, the negative electrode of the electrochromic layer is electrically connected to the S1 and S4 contacts, and the positive electrode of the electrochromic layer is electrically connected to the S2 contact and the S3 contact; the threshold voltage of the single-chip microcomputer is set, so that when the intensity of sunlight irradiated on the electrochromic glass is high, the voltage provided by the organic solar cell layer is higher than the threshold voltage, and the single-chip microcomputer controls the relay so that the anode of the organic solar cell layer is electrically connected to the S1 contact and The cathode is electrically connected to the S3 contact, thereby forming a forward current in the electrochromic layer to cause the electrochromic layer to color, thereby reducing the transparency of the electrochromic glass; when the intensity of sunlight irradiating the electrochromic glass is weak, the voltage provided by the organic solar cell layer is lower than the threshold voltage, and the single-chip computer controls the relay so that the anode of the organic solar cell layer is electrically connected to the S2 contact and the cathode is electrically connected to the S4 contact, thereby forming a reverse current in the electrochromic layer to cause the electrochromic layer to fade, thereby increasing the transparency of the electrochromic glass.
[0028] According to the present invention, in order to improve the performance of the electrochromic glass, preferably, the organic solar cell layer includes a first transparent electrode layer (i.e., an anode), a hole transport layer, a photoelectric active layer, an electron transport layer and a second transparent electrode layer (i.e., a cathode) arranged layer by layer, and the electrochromic layer includes a positive electrode, an electrochromic active layer, a negative electrode and a glass layer arranged layer by layer.
[0029] According to the present invention, in order to improve the photoelectric conversion efficiency of the organic solar cell layer, better supply power to the electrochromic layer, and achieve a better electrochromic effect, preferably, the photoelectric active layer includes an electron donor material and an electron acceptor material.
[0030] Preferably, the electron donor material is one or more polymers containing repeating structural units represented by formula (1):
[0031] Formula (1)
[0032] Wherein, the A group is selected from one of the structures shown in formula (1-a), formula (1-b) and formula (1-c):
[0033]
[0034] The electron acceptor material is one or more of the conjugated macromolecules shown in formula (2):
[0035] Formula (2)
[0036] Among them, the B group and the C group form a conjugated structure;
[0037] The B group is selected from one of the structures shown in formula (2-a), formula (2-b) and formula (2-c):
[0038]
[0039] The C group is selected from 1 to 3 conjugated structures formed by formula (2-d) or is absent:
[0040]
[0041] The D group is selected from the group shown in formula (2-e) or is absent:
[0042]
[0043] The E group is selected from the group represented by formula (2-f):
[0044]
[0045] Wherein, each R1, R2, R3, R4, R5, R6, R7, R8 and R9 is independently selected from H, C1-C30 alkyl, C6-C30 aryl and C1-C30 alkoxy or alkylthio; each X1, X2, X3, X4, X5, X6, X7, X8 and X9 is independently selected from O, S and Se; each Y1, Y2 and Y3 is independently selected from H and halogen atoms.
[0046] More preferably, each R1, R2, R3, R4, R5, R6, R7, R8 and R9 is each independently selected from H, a C1-C20 alkyl group, a C6-C20 aryl group and a C1-C20 alkoxy or alkylthio group; each X1, X2, X3, X4, X5, X6, X7, X8 and X9 is each independently selected from O, S and Se; each Y1, Y2 and Y3 is each independently selected from H, F, Cl and Br.
[0047] Further preferably, each R1, R2, R3, R4, R5, R6, R7, R8 and R9 is each independently selected from H, a C6-C12 alkyl group, a C6-C12 aryl group and a C6-C12 alkoxy group or alkylthio group; each X1, X2, X3, X4, X5, X6, X7, X8 and X9 is each independently selected from O, S and Se; each Y1, Y2 and Y3 is each independently selected from H, F and Cl.
[0048] Still further preferably, each of R1, R2, R3, R4, R5, R6, R7, R8 and R9 is independently selected from H, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, 2-ethylhexyl, 2-n-butyloctyl, n-hexyloxy, 2-ethylhexyloxy, n-nonyloxy, n-undecyloxy, n-hexylthio, n-nonylthio, n-undecylthio, p-n-propylphenyl and p-n-hexylphenyl.
[0049] According to the present invention, in order to make the electron donor material and the electron acceptor material form a better match and improve the performance of the photoelectric active layer, preferably, the mass ratio of the electron donor material to the electron acceptor material is 1:1-10, preferably 1:1.5-5, for example, it can be 1:1.5, 1:3, 1:4 and 1:5 and the range of any values therebetween.
[0050] According to the present invention, in order to further improve the performance of the electron donor material and enhance the synergistic effect between the electron donor material and the electron acceptor, preferably, the weight average molecular weight of the polymer containing the repeating structural unit represented by formula (1) is 10000-200000 g / mol, more preferably 20000-180000 g / mol, and further preferably 30000-150000 g / mol (for example, 35000 g / mol, 40000 g / mol, 50000 g / mol, 80000 g / mol, 100000 g / mol, 120000 g / mol, 150000 g / mol and the like, and the range between any values thereof); preferably, the PDI (molecular weight distribution coefficient) of the polymer containing the repeating structural unit represented by formula (1) is 1-5, preferably 1-4, and more preferably 1-3 (for example, it can be 1.2, 1.7, 2.3, 2.7 and the like, and the range between any values thereof).
[0051] According to the present invention, preferably, the electron donor material is selected from one or more polymers containing repeating structural units represented by formula (1-1), formula (1-2) and formula (1-3):
[0052] Formula (1-1)
[0053] Formula (1-2)
[0054] Formula (1-3)
[0055] More preferably, the electron donor material is selected from one or more polymers containing repeating structural units represented by formula (1-1-1), formula (1-2-1) and formula (1-3-1):
[0056] Formula (1-1-1)
[0057] Formula (1-2-1)
[0058] Formula (1-3-1)
[0059] Among them, -C4H9 is n-butyl, -C6H 13 It is n-hexyl.
[0060] In the case where the electron donor material is preferably a polymer containing repeating structural units of formula (1-1), the weight average molecular weight of the polymer containing repeating structural units of formula (1-1) more preferably used in the present invention is 10000-80000 g / mol, more preferably 20000-60000 g / mol, and further preferably 30000-50000 g / mol (for example, 26000 g / mol, 38600 g / mol, 45000 g / mol, and the range between any values thereof); preferably, the PDI (molecular weight distribution coefficient) of the polymer containing repeating structural units of formula (1-1) is 1-3, preferably 1-2.8, and more preferably 1-2.5 (for example, it can be 1.2, 1.7, 2.1, 2.4, and the range between any values thereof).
[0061] In the case where the electron donor material is preferably a polymer containing repeating structural units of formula (1-2), the weight average molecular weight of the polymer containing repeating structural units of formula (1-2) more preferably used in the present invention is 20,000-180,000 g / mol, more preferably 40,000-160,000 g / mol, and further preferably 60,000-140,000 g / mol (for example, 65,000 g / mol, 100,000 g / mol, 124,000 g / mol, and any ranges between these values); preferably, the PDI (molecular weight distribution coefficient) of the polymer containing repeating structural units of formula (1-2) is 1-3, preferably 1-2.8, and more preferably 1-2.5 (for example, it can be 1.2, 1.7, 2.1, 2.4, and any ranges between these values).
[0062] In the case where the electron donor material is preferably a polymer containing repeating structural units of formula (1-3), the weight average molecular weight of the polymer containing repeating structural units of formula (1-3) more preferably used in the present invention is 10000-80000 g / mol, more preferably 20000-60000 g / mol, and further preferably 30000-50000 g / mol (for example, 35000 g / mol, 38000 g / mol, 46000 g / mol, etc., and ranges between any values thereof); preferably, the PDI (molecular weight distribution coefficient) of the polymer containing repeating structural units of formula (1-3) is 1-3, preferably 1-2.8, and more preferably 1-2.5 (for example, it can be 1.2, 1.7, 2.1, 2.4, etc., and ranges between any values thereof).
[0063] According to the present invention, preferably, the electron acceptor material is one or more of the structures shown in formula (2-1), formula (2-2), formula (2-3), formula (2-4) and formula (2-5):
[0064] Formula (2-1)
[0065] Formula (2-2)
[0066] Formula (2-3)
[0067] Formula (2-4)
[0068] Formula (2-5)
[0069] More preferably, the electron acceptor material is one or more of the structures shown in formula (2-1-1), formula (2-1-2), formula (2-1-3), formula (2-1-4) and formula (2-2-1):
[0070] Formula (2-1-1)
[0071] Formula (2-1-2)
[0072] Formula (2-1-3)
[0073] Formula (2-1-4)
[0074] Formula (2-2-1)
[0075] Among them, -C4H9 is n-butyl; -C6H 13 Is n-hexyl; -C9H 19 is n-nonyl; -C 11 H 23 It is n-undecyl.
[0076] According to the present invention, the polymer composed of the repeating structural units shown in formula (1-1-1) is also called PM6; the polymer composed of the repeating structural units shown in formula (1-2-1) is also called PTB7-Th; the polymer composed of the repeating structural units shown in formula (1-3-1) is also called D18; the compound shown in formula (2-1-1) is also called L8-BO; the compound shown in formula (2-1-2) is also called BTP-eC9; the compound shown in formula (2-1-3) is also called Y6; the compound shown in formula (2-1-4) is also called BO-4Cl; the compound shown in formula (2-2-1) is also called IEICO-4F.
[0077] The above organic substances can be commercially available or prepared by conventional methods in the art disclosed in the literature. For example, PM6 can be prepared by the method provided in the literature "Adv. Mater. 2015, 27, 4655-4660"; PTB7-Th can be prepared by the method provided in the literature "Adv. Mater. 2013, 25, 4766-4771"; D18 can be prepared by the method provided in the literature "Sci. Bull. 2020, 65, 272-275"; L8-BO can be prepared by the method provided in the literature "Nat. Energy 2021, 6, 605"; Y6 can be prepared by the method provided in the literature "Joule 2019,3,1140-1151"; BTP-eC9 and BO-4Cl can be prepared by the method provided in the document "Adv.Mater.2020,32,1908205"; IEICO-4F can be prepared by the method provided in the document "Angew.Chem.Int.Ed.2017,56,3045".
[0078] According to the present invention, in order to make the organic solar cell layer and the electrochromic layer form a better coordination, on the one hand, the photoelectric conversion efficiency of the organic solar cell layer is improved, and on the other hand, the color changing performance of the electrochromic layer is improved, thereby obtaining a more sensitive electrochromic glass, the materials of the other layers can be selected.
[0079] According to the present invention, when the first transparent electrode layer or the second transparent electrode layer is used as one end away from the electrochromic layer, its transparent electrode material can be selected within a wider range. In order to form a better organic solar cell layer, preferably, the transparent electrode material of the first transparent electrode layer or the second transparent electrode layer can be selected from one or more of indium tin oxide glass, indium zinc oxide glass and indium tungsten oxide glass.
[0080] According to the present invention, the hole transport material of the hole transport layer can be selected in a wide range. In order to obtain good hole mobility and improve the photoelectric efficiency of the organic solar cell layer, preferably, the hole transport material of the hole transport layer can be selected from one or more of poly(3,4-ethylenedioxythiophene)-(polystyrene sulfonate), [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, CuSCN and MoO3. Among them, poly(3,4-ethylenedioxythiophene)-(polystyrene sulfonate) can also be called PEDOT:PSS (Al4083), which can be purchased from Heraeus Inc.
[0081] According to the present invention, the electron transport material of the electron transport layer can be selected in a wide range. In order to improve the electron migration rate, preferably, the electron transport material of the electron transport layer can be selected from ZnO, diphenylphosphine oxide, poly (9,9-bis (3'- (N, N-dimethyl) -N-ethylaminopropyl -2,7-fluorene) -alt-2,7- (9,9-dioctylfluorene)) dibromide and 2,9-bis (3- ((3- (dimethylamino) propyl) amino) propyl) -3,3'- (1,3,8,10-tetraintracontano [2,1,9-DEF: 6,5,10-D' E'F'] diisoquinoline. Among them, diphenylphosphine oxide can also be called DPO, poly (9,9-bis (3'- (N, N-dimethyl) -N-ethylaminopropyl -2,7-fluorene) -alt-2,7- (9,9-dioctylfluorene)) dibromide can also be called PFN-Br, 2,9-bis (3- ((3- (dimethylamino) propyl) amino) propyl) -3,3'- (1,3,8,10-tetraindole [2,1,9-DEF:6,5,10-D'E'F'] diisoquinoline can also be called PDINN, PDINN can be purchased from Solarmer Materials (Beijing) Inc.
[0082] According to the present invention, in order to stack the organic solar cell layer and the electrochromic layer to obtain an integrated electrochromic glass, preferably, the first transparent electrode layer or the second transparent electrode layer and the positive electrode are two conductive surfaces of a double-sided conductive glass. For example, when the solar cell layer is a forward structure, the second transparent electrode layer and the positive electrode are two conductive surfaces of a double-sided conductive glass, such as Figure 1 and 2 As shown, the upper conductive surface of the double-sided conductive glass provides a second transparent electrode layer, and the lower conductive surface of the double-sided conductive glass provides the positive electrode. For another example, when the solar cell layer is a reverse structure (not shown), the first transparent electrode layer and the positive electrode are two conductive surfaces of the double-sided conductive glass, the upper conductive surface of the double-sided conductive glass provides the first transparent electrode layer, and the lower conductive surface of the double-sided conductive glass provides the positive electrode. In this way, the integrated design of the organic solar cell layer and the electrochromic layer can be better realized, but it should be understood that the upper and lower conductive surfaces of the double-sided conductive glass are not directly electrically connected, but can be controllably indirectly electrically connected through external wires, etc. More preferably, the double-sided conductive glass is selected from one or more of double-sided indium tin oxide glass, double-sided indium zinc oxide glass and double-sided indium tungsten oxide glass.
[0083] According to the present invention, the electrochromic active layer can be selected in a wide range as long as it can achieve the electrochromic function. In order to better cooperate with the organic solar cell layer and improve the thermal insulation performance, preferably, Figure 3 As shown, the electrochromic active layer includes a peripheral frame and an internal cavity, and the internal cavity is provided with an electrochromic electrolyte.
[0084] The material of the outer frame can be selected from a wide range. In order to facilitate the injection of the electrochromic electrolyte, the material of the outer frame is generally rubber, for example, a styrene-butadiene rubber outer frame can be used.
[0085] Wherein, under normal circumstances, the electrochromic electrolyte includes an electrochromic material and a gel polymer electrolyte. According to the present invention, preferably, the content of the electrochromic material is 2-16wt%, preferably 4-12wt%; the content of the gel polymer electrolyte is 0.05-2wt%, preferably 0.1-1.2wt%. Wherein, the electrochromic material can be selected from a variety of electrochromic materials, for example, it can be a metal oxide, an inorganic salt and an organic electrochromic material, preferably one or more of CuCl2, BiCl3, LiBr, LiCl, LiClO4, Cu(ClO4)2 and viologen derivatives, more preferably one or more of CuCl2, BiCl3 and viologen derivatives. The gel polymer electrolyte can be selected from one or more of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene oxide and hydroxyethyl cellulose, preferably polyvinyl alcohol and / or polyvinyl pyrrolidone. Preferably, the weight average molecular weight of the gel polymer electrolyte is 20000-60000 g / mol (for example, it can be 20000 g / mol, 44000 g / mol, 50000 g / mol and 60000 g / mol and the range between any values thereof), and the PDI is 1.02-1.2 (for example, it can be 1.02, 1.08, 1.1, 1.12 and 1.2 and the range between any values thereof).
[0086] The electrochromic electrolyte may further contain an acidic additive, such as one or more of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a nitric acid aqueous solution, etc. The concentration of the acidic additive may be, for example, 30-50wt%, and the amount may be, for example, 0.05-0.2wt%.
[0087] The solvent of the electrochromic electrolyte may be selected from one or more of water, acetonitrile, N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide, preferably water and / or dimethyl sulfoxide.
[0088] According to the present invention, the conductive material of the negative electrode can be selected from a wide range. Preferably, the conductive material of the negative electrode is selected from one or more of a conductive copper strip, a conductive aluminum strip, a conductive silver strip and a conductive gold strip, preferably a conductive copper strip and / or a conductive aluminum strip.
[0089] According to the present invention, the glass material of the glass layer can be selected from a wide range, for example, the glass material of the glass layer can be selected from ordinary glass.
[0090] To this end, in a preferred embodiment of the present invention, the electrochromic layer structure includes a conductive glass positive electrode arranged in sequence, a peripheral frame arranged around the conductive surface of the conductive glass positive electrode, an electrochromic electrolyte arranged in the internal cavity surrounded by the peripheral frame, a negative electrode (which can be a coil surrounded by a conductive tape) arranged at the other end of the peripheral frame away from the conductive glass positive electrode, and the negative electrode is in contact with the electrochromic electrolyte, and a glass layer is arranged outside the negative electrode. Thus, the conductive surface of the conductive glass positive electrode and the negative electrode conductive tape can be connected to a wire, and a power source, such as the organic solar cell layer of the present invention, is arranged between them to supply power to the electrochromic layer.
[0091] According to the present invention, in order to further improve the performance of the electrochromic glass, the thickness of each layer can be adjusted to form a better match between the layers and control the overall thickness and weight of the electrochromic glass. Preferably, the thickness of the photoelectric active layer is 40-120nm, more preferably 60-90nm, for example, it can be 60nm, 70nm, 80nm and 90nm and any range therebetween.
[0092] Preferably, the thickness of the hole transport layer is 25-50 nm, preferably 25-35 nm, for example, 27 nm, 30 nm, 32 nm, 34 nm, and any range therebetween.
[0093] Preferably, the thickness of the electron transport layer is 10-50 nm, preferably 20-40 nm, for example, 20 nm, 30 nm, 35 nm, 40 nm, and any range therebetween.
[0094] Preferably, the thickness of the electrochromic active layer is 0.01-5 mm, preferably 0.1-3 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, and any range therebetween.
[0095] According to the present invention, the first transparent electrode layer is the anode of the organic solar cell layer, and the second transparent electrode layer is the cathode of the organic solar cell layer.
[0096] A second aspect of the present invention provides a method for preparing the electrochromic glass, which comprises preparing the electrochromic layer and the organic solar cell layer and setting the control circuit to obtain the electrochromic glass.
[0097] According to the present invention, preferably, the method comprises sequentially preparing the electron transport layer, the photoelectric active layer, the hole transport layer and the first transparent electrode layer on one conductive surface of the double-sided conductive glass to obtain the organic solar cell layer, or sequentially preparing the hole transport layer, the photoelectric active layer, the electron transport layer and the second transparent electrode layer on one conductive surface of the double-sided conductive glass to obtain the organic solar cell layer; and preparing the electrochromic active layer, the negative electrode and the glass layer on the other conductive surface of the double-sided conductive glass to obtain the electrochromic layer.
[0098] More preferably, the method comprises providing an electron transport material on one conductive surface of the double-sided conductive glass and performing a first thermal annealing treatment to form the electron transport layer, providing the electron donor material and the electron acceptor material on the electron transport layer and performing a second thermal annealing treatment to form the photoelectric active layer, providing a hole transport material on the photoelectric active layer to form the hole transport layer, providing a transparent electrode material on the hole transport layer and performing a thermal lamination treatment to form the first transparent electrode layer, thereby preparing the organic solar cell layer, or providing a hole transport material on one conductive surface of the double-sided conductive glass and performing a first thermal annealing treatment to form the hole transport layer, providing a hole transport material on the hole transport layer and performing a thermal lamination treatment to form the first transparent electrode layer. The electron donor material and the electron acceptor material are provided on the transport layer and a second thermal annealing treatment is performed to form the photoelectric active layer, an electron transport material is provided on the photoelectric active layer to form the electron transport layer, a transparent electrode material is provided on the electron transport layer and a thermal lamination treatment is performed to form the second transparent electrode layer, thereby obtaining the organic solar cell layer; the outer frame is provided on the other conductive surface of the double-sided conductive glass, a glass material sealed with a negative electrode material is provided on the outer frame to form the negative electrode and the glass layer thereon, and the electrochromic electrolyte is injected into the internal cavity surrounded by the outer frame to form the electrochromic active layer, thereby obtaining the electrochromic layer.
[0099] According to the present invention, in order to better form an electron transport layer, preferably, the electron transport material is provided in the form of a solution. When the electron transport material is a metal oxide such as ZnO, the concentration of its solution is 5-65 mg / mL, preferably 15-30 mg / mL, for example, it can be 15 mg / mL, 20 mg / mL, 25 mg / mL and 30 mg / mL and the range between any values thereof. When the electron transport material is an organic material such as PDINN, the concentration of its solution is 0.1-20 mg / mL, preferably 0.3-10 mg / mL, for example, it can be 0.5 mg / mL, 1 mg / mL, 5 mg / mL, 8 mg / mL and 10 mg / mL and the range between any values thereof. Preferably, the amount of the solution of the electron transport material is 0.5-5 mL, preferably 1-3 mL, for example, it can be 1 mL, 2 mL, 2.5 mL and 3 mL and the range between any values thereof. Preferably, the solvent of the electron transport material solution is selected from one or more of n-butanol, chlorobenzene, chloroform, xylene, acetone and methanol.
[0100] According to the present invention, in order to obtain an electron transport layer or a hole transport layer in a better state to facilitate performance improvement, preferably, the conditions of the first thermal annealing treatment include: temperature 120-230°C, time 10-80min; preferably temperature 150-200°C (for example, it can be 150°C, 170°C, 180°C and 200°C and the range between any values thereof), time 20-60min (for example, it can be 20min, 40min, 50min and 60min and the range between any values thereof).
[0101] According to the present invention, in order to better form the photoelectric active layer and enhance the activity of the photoelectric active layer, preferably, the electron donor material and the electron acceptor material are provided in the form of a mixed solution, in which the concentration of the electron donor material is 2-10 mg / mL, preferably 4-6 mg / mL (for example, it can be 4 mg / mL, 5 mg / mL and 6 mg / mL and the range between any values thereof), and the concentration ratio of the electron donor material to the electron acceptor material is 1:1-10, preferably 1:1.5-5 (for example, it can be 1:1.5, 1:1.8, 1:2.5 and 1:5 and the range between any values thereof). Preferably, the amount of the mixed solution of the electron donor material and the electron acceptor material is 0.5-2 mL, preferably 0.8-1.5 mL, for example, it can be 0.8 mL, 1 mL, 1.2 mL and 1.5 mL and the range between any values thereof. Preferably, the solvent of the mixed solution of the electron donor material and the electron acceptor material is selected from one or more of chlorobenzene, chloroform, xylene, acetone and methanol.
[0102] According to the present invention, in order to improve the performance and efficiency of the photoelectric active layer, preferably, the conditions of the second thermal annealing treatment include: temperature 70-130°C, time 2-8min; preferably temperature 80-120°C (for example, it can be 80°C, 90°C, 100°C and 120°C and the range between any values thereof), time 4-6min (for example, it can be 4min, 5min and 6min and the range between any values thereof).
[0103] According to the present invention, in order to form a better hole transport layer, preferably, the hole transport material is provided in the form of a solution, and the concentration of the solution of the hole transport material is 0.5-50 mg / mL, preferably 1-10 mg / mL, for example, it can be 1 mg / mL, 2.5 mg / mL, 5 mg / mL and 10 mg / mL and the range between any values thereof. Preferably, the amount of the solution of the hole transport material is 0.1-10 mL, preferably 0.2-1 mL, for example, it can be 0.2 mL, 0.4 mL, 0.6 mL and 1 mL and the range between any values thereof. Preferably, the solvent of the solution of the hole transport material is selected from one or more of water, chlorobenzene, chloroform, xylene, acetone, ethanol and methanol.
[0104] According to the present invention, preferably, the conditions of the heat lamination treatment include: temperature 70-150°C, time 2-30min, pressure 10-1000kPa; preferably temperature 80-120°C (for example, it can be 80°C, 90°C, 105°C and 120°C and the range between any values thereof), time 5-20min (for example, it can be 5min, 10min, 15min and 20min and the range between any values thereof), pressure 50-500kPa (for example, it can be 50kPa, 100kPa, 300kPa and 500kPa and the range between any values thereof).
[0105] According to the present invention, in the layer-by-layer processing, preferably, when providing the electron transport material, the electron donor material, the electron acceptor material, and the hole transport material, the method adopted may be spin coating, scraping, printing or sputtering, preferably spin coating. More preferably, the spin coating conditions of the electron transport layer (i.e., the electron transport material) are a rotation speed of 2000-4000rpm and a time of 15-30s; the spin coating conditions of the photoelectric active layer (i.e., the electron donor material and the electron acceptor material) are a rotation speed of 2000-4000rpm and a time of 20-40s; and the spin coating conditions of the hole transport layer (i.e., the hole transport material) are a rotation speed of 3000-6000rpm and a time of 15-50s.
[0106] The present invention combines a semi-transparent organic solar cell with an electrochromic device and obtains an electrochromic glass with an integrated semi-transparent organic solar cell by setting a specific control circuit. The electrochromic glass can use the semi-transparent organic solar cell to convert the absorbed light energy into electrical energy, which not only reduces the thermal effect of sunlight, but also provides electrical energy for the electrochromic device. At the same time, the control circuit can adjust the direction of the current flowing through the electrochromic device according to the intensity of sunlight, thereby adjusting the transparency of the electrochromic glass. The electrochromic glass of the present invention can realize intelligent dimming, darken when the light is strong to block the strong light, and become transparent when the light is weak to have a high transmittance. The electrochromic glass of the present invention also has excellent heat insulation performance, can achieve the effect of energy saving and carbon reduction, and is suitable for use as a glass window in the field of construction.
[0107] The present invention will be described in detail below through examples.
[0108] In the following example:
[0109] Using the SS-X50 solar simulator and AM1.5G solar spectrum filter from Guangyan Technology Company, at 100mWcm -2 The device is tested for solar cell performance under light intensity, where the light intensity is calibrated using a standard polycrystalline silicon solar cell (SRC2020).
[0110] The UV-visible absorption spectra and visible light transmission spectra were measured using a Shimadzu UV-2600i UV-visible spectrophotometer.
[0111] The IV curve is measured by a Keysight B2901A precision current source meter. Parameters such as short-circuit current, open-circuit voltage, fill factor, and photoelectric conversion efficiency can be obtained from the IV curve.
[0112] The electrochemical cyclic voltammetry curves were measured using a Shanghai Chenhua CHI660E electrochemical workstation.
[0113] All materials can be commercial products or prepared by conventional methods in the art disclosed in the literature, among which indium tin oxide glass and double-sided indium tin oxide glass were purchased from Shenzhen South China Xiangcheng Technology Co., Ltd. PEDOT:PSS (Al4083) was purchased from Heraeus Inc. The electron donor materials PM6, PTB7-Th and the electron acceptor materials BTP-eC9, IEICO-4F can be commercial products or prepared by conventional methods in the art disclosed in the literature. PM6 can be prepared by the method provided in the document "Adv. Mater. 2015, 27, 4655-4660" (weight average molecular weight is 38600 g / mol, PDI=2); PTB7-Th can be prepared by the method provided in the document "Adv. Mater. 2013, 25, 4766-4771" (weight average molecular weight is 124000 g / mol, PDI=1.7); BTP-eC9 can be prepared by the method provided in the document "Adv. Mater. 2020, 32, 1908205"; IEICO-4F can be prepared by the method provided in the document "Angew. Chem. Int. Ed. 2017, 56, 3045".
[0114] The thickness of the electron transport layer is 35 nm, and the spin coating conditions are a rotation speed of 3000 rpm and a time of 30 s; the thickness of the photoelectric active layer is 80 nm, and the spin coating conditions are a rotation speed of 3000 rpm and a time of 30 s; the thickness of the hole transport layer is 30 nm, and the spin coating conditions are a rotation speed of 4000 rpm and a time of 30 s; the thickness of the electrochromic active layer is 2 mm.
[0115] Example 1
[0116] 1 mL of 15 mg / mL ZnO solution (solvent is n-butanol) was spin-coated on one side of the double-sided indium tin oxide glass (the conductive surface is the second transparent electrode layer) and thermally annealed to obtain an electron transport layer (thermal annealing conditions: temperature 200°C, time 60 min). Subsequent operations were then continued in a glove box filled with nitrogen. 5 mg of PM6 and 12 mg of BTP-eC9 were dissolved in 1 mL of chlorobenzene to obtain a mixed solution (PM6 concentration of 5 mg / mL, BTP-eC9 concentration of 12 mg / mL), which was then spin-coated on the electron transport layer and thermally annealed to obtain a photoelectric active layer (thermal annealing conditions: temperature 100°C, time 5 min). 0.2 mL of 5 mg / mL PEDOT:PSS (Al4083) solution (solvent is water and ethanol) was spin-coated on the photoelectric active layer to obtain a hole transport layer. Finally, a piece of indium tin oxide glass was thermally laminated onto the hole transport layer to obtain a first transparent electrode layer (thermal lamination conditions: temperature 105° C., time 10 min, pressure 50 kPa), and finally an organic solar cell layer with a positive structure was obtained.
[0117] The styrene-butadiene rubber peripheral frame is bonded to the other side of the double-sided indium tin oxide glass by an adhesive, and then the ordinary glass sealed with a conductive copper tape is bonded to the styrene-butadiene rubber peripheral frame to obtain a negative electrode and a glass layer, and finally an electrochromic electrolyte is injected into the butyl rubber peripheral frame to obtain an electrochromic active layer, and finally an electrochromic layer is obtained. The preparation process of the electrochromic electrolyte is as follows: 0.2g of CuCl2, 0.158g of BiCl3, 8.69g of LiBr and 84μL of hydrochloric acid aqueous solution (concentration of 38.5wt%) are dissolved in 90mL of water at room temperature to obtain solution A, 0.15g of polyvinyl alcohol (weight average molecular weight 44000g / mol, PDI is 1.05) is dissolved in 10mL of water at 90°C to obtain solution B, and solution A and solution B are mixed to obtain an electrochromic electrolyte.
[0118] The above-prepared device is equipped with a control circuit to obtain an electrochromic glass with an integrated semi-transparent organic solar cell, the structure of which is as follows: Figure 1 and Figure 2 The two control circuits are shown below.
[0119] Control circuit for manual regulation: Figure 4 As shown, the control circuit includes a universal conversion switch, and the universal conversion switch includes eight contacts. Among them, the anode of the organic solar cell layer (i.e., the first transparent electrode layer mentioned above) is electrically connected to the first contact 1 and the fifth contact 5, the cathode of the organic solar cell layer (i.e., the second transparent electrode layer mentioned above) is electrically connected to the third contact 3 and the seventh contact 7, the negative electrode of the electrochromic layer (i.e., the conductive copper strip mentioned above) is electrically connected to the second contact 2 and the fourth contact 4, and the positive electrode of the electrochromic layer (i.e., the side of the double-sided indium tin oxide glass close to the electrochromic layer) is electrically connected to the sixth contact 6 and the eighth contact 8. Therefore, when the universal conversion switch connects the first contact 1 and the second contact 2 and the seventh contact 7 and the eighth contact 8, the voltage provided by the organic solar cell layer causes a forward current to be formed in the electrochromic layer to cause the electrochromic layer to color, thereby reducing the transparency of the electrochromic glass; when the universal conversion switch connects the third contact 3 and the fourth contact 4 and the fifth contact 5 and the sixth contact 6, the voltage provided by the organic solar cell layer causes a reverse current to be formed in the electrochromic layer to cause the electrochromic layer to fade, thereby increasing the transparency of the electrochromic glass.
[0120] Control circuits for automatic regulation: Figure 5As shown, the control circuit includes a voltage controller, which includes two relays and a single-chip microcomputer. Each relay includes two contacts. The negative pole of the electrochromic layer (i.e., the conductive copper tape mentioned above) is electrically connected to the S1 and S4 contacts, and the positive pole of the electrochromic layer (i.e., the side of the double-sided indium tin oxide glass close to the electrochromic layer) is electrically connected to the S2 contact and the S3 contact. The threshold voltage of the single chip microcomputer is set, so that when the intensity of sunlight irradiating the electrochromic glass is high, the voltage provided by the organic solar cell layer is higher than the threshold voltage, and the single chip microcomputer controls the relay so that the anode (i.e., the above-mentioned first transparent electrode layer) of the organic solar cell layer is electrically connected to the S1 contact and the cathode (i.e., the above-mentioned second transparent electrode layer) is electrically connected to the S3 contact, thereby forming a forward current in the electrochromic layer to cause the electrochromic layer to be colored, thereby reducing the transparency of the electrochromic glass; when the intensity of sunlight irradiating the electrochromic glass is weak, the voltage provided by the organic solar cell layer is lower than the threshold voltage, and the single chip microcomputer controls the relay so that the anode (i.e., the above-mentioned first transparent electrode layer) of the organic solar cell layer is electrically connected to the S2 contact and the cathode (i.e., the above-mentioned second transparent electrode layer) is electrically connected to the S4 contact, thereby forming a reverse current in the electrochromic layer to cause the electrochromic layer to fade, thereby increasing the transparency of the electrochromic glass.
[0121] The IV curve of an organic solar cell layer is as follows Figure 6 As shown, through Figure 6 The IV curve shown can be used to obtain the open circuit voltage V of the organic solar cell layer. OC is 0.807V, short-circuit current J SC 11.9 mA cm -2 , the filling factor FF is 54.8%, and the photoelectric conversion efficiency PCE is 5.3%.
[0122] The transmission spectrum of the organic solar cell layer is as follows Figure 7 As shown, the average visible light transmittance is 47.8%.
[0123] The cyclic voltammetry curve of the electrochromic layer is as follows Figure 8 shown.
[0124] The transmission spectra of electrochromic glass in the tinted and faded states are as follows: Fig. 9 As shown, when the electrochromic glass is in a tinted state, the average visible light transmittance is 0; when it is in a faded state, the average visible light transmittance is 38.2%.
[0125] Example 2
[0126] According to the method of Example 1, the difference is that the preparation process of the solar cell layer is: 0.2 mL of 5 mg / mL PEDOT:PSS (Al4083) solution (solvent is water) is taken and all spin-coated on one surface of the double-sided indium tin oxide glass (the conductive surface is the first transparent electrode layer) and thermally annealed to obtain a hole transport layer (thermal annealing conditions: temperature 150°C, time 20min). Subsequent operations are then continued in a glove box filled with nitrogen. 10 mg of PM6 and 12 mg of BTP-eC9 are dissolved in 1 mL of chlorobenzene to obtain a mixed solution (PM6 concentration is 10 mg / mL, BTP-eC9 concentration is 12 mg / mL), and then all of it is spin-coated on the hole transport layer and thermally annealed to obtain a photoelectric active layer (thermal annealing conditions: temperature 100°C, time 5min). 1 mL of 15 mg / mL ZnO solution (solvent is n-butanol) is taken and all spin-coated on the photoelectric active layer to obtain an electron transport layer. Finally, a piece of indium tin oxide glass was thermally laminated onto the hole transport layer to obtain a second transparent electrode layer (thermal lamination conditions: temperature 105° C., time 10 min, pressure 50 kPa), and finally an organic solar cell layer with a reverse structure was obtained.
[0127] According to the method of Example 1, an electrochromic layer is prepared on the other side of the double-sided conductive glass, and a control circuit is set up to finally obtain an electrochromic glass.
[0128] The IV curve of an organic solar cell layer is as follows Fig.10 As shown, through Fig.10 The IV curve shown can be used to obtain the open circuit voltage V of the organic solar cell layer. OC is 0.769V, short-circuit current J SC 16.2 mA cm -2 , the filling factor FF is 38.3%, and the photoelectric conversion efficiency PCE is 4.8%.
[0129] The transmission spectrum of organic solar cell layers is as follows Fig.11 As shown, the average visible light transmittance is 34.2%.
[0130] Example 3
[0131] According to the method of Example 1, the difference is that PM6 is replaced by PTB7-Th, and BTP-eC9 is replaced by IEICO-4F, and finally electrochromic glass with integrated semi-transparent organic solar cells is prepared.
[0132] The IV curve of an organic solar cell layer is as follows Fig.12 As shown, through Fig.12 The IV curve shown can be used to obtain the open circuit voltage V of the organic solar cell layer. OC is 0.686V, short-circuit current JSC 13.2 mA cm -2 , the fill factor FF is 54.3% and the photoelectric conversion efficiency PCE is 4.9%.
[0133] The transmission spectrum of organic solar cell layers is as follows Fig.13 As shown, the average visible light transmittance is 43.8%.
[0134] Test Case
[0135] This test example is used to evaluate the thermal insulation performance of electrochromic glass.
[0136] The electrochromic glass prepared in Example 1 was placed on a 2 Hole insulated foam box (size 13*11*11cm 3 ), and a black dovetail clip was placed in the center of the foam box as a heat absorber. The foam box was then exposed to simulated sunlight for continuous irradiation. Ordinary glass and the electrochromic glass prepared in Example 1 were used as filters at the aperture, respectively, and an infrared camera (FLIR-T600) was used to capture and record the infrared image and surface temperature of the sample. The thermal insulation properties of ordinary glass and the electrochromic glass prepared in Example 1 under different conditions are shown in Figure 2. Fig.14 As shown. It can be seen that when ordinary glass is used as a filter, the temperature of the black dovetail clip rises rapidly from 25°C to 37.6°C when it is illuminated for three minutes, and reaches 41.4°C ten minutes later, with a temperature increase of 16.4°C. When the electrochromic glass prepared in Example 1 is used as a filter, the temperature of the black dovetail clip when it is illuminated for three minutes in the faded and colored states is only 27.2°C and 25.5°C, respectively, and reaches 28.2°C and 26.2°C, respectively, ten minutes later, with a temperature increase of 3.2°C and 1.2°C, respectively. It can be seen that the electrochromic glass prepared by the present invention has good thermal insulation properties, and can be used in building windows to greatly reduce indoor energy consumption.
[0137] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An electrochromic glass with integrated semi-transparent organic solar cells, characterized in that: The electrochromic glass comprises an electrochromic layer and an organic solar cell layer stacked thereon, and the organic solar cell layer supplies power to the electrochromic layer; The electrochromic glass is also provided with a control circuit, which can change the connection mode between the positive and negative electrodes of the organic solar cell layer and the electrodes of the electrochromic layer, so as to adjust the current direction in the electrochromic layer to achieve coloring or fading.
2. The electrochromic glass according to claim 1, wherein: The control circuit is configured such that: when the intensity of sunlight irradiating the electrochromic glass is high, the voltage provided by the organic solar cell layer causes a forward current to be formed in the electrochromic layer to cause the electrochromic layer to be colored, thereby reducing the transparency of the electrochromic glass; when the intensity of sunlight irradiating the electrochromic glass is weak, the voltage provided by the organic solar cell layer causes a reverse current to be formed in the electrochromic layer to cause the electrochromic layer to fade, thereby increasing the transparency of the electrochromic glass.
3. The electrochromic glass according to claim 1 or 2, wherein: The control circuit includes a universal conversion switch, and the universal conversion switch includes eight contacts; The anode of the organic solar cell layer is electrically connected to the first contact (1) and the fifth contact (5), the cathode of the organic solar cell layer is electrically connected to the third contact (3) and the seventh contact (7), the cathode of the electrochromic layer is electrically connected to the second contact (2) and the fourth contact (4), and the anode of the electrochromic layer is electrically connected to the sixth contact (6) and the eighth contact (8); Thus, when the universal switch is turned on to connect the first contact (1) and the second contact (2) and the seventh contact (7) and the eighth contact (8), the voltage provided by the organic solar cell layer causes a forward current to be formed in the electrochromic layer to cause the electrochromic layer to be colored, thereby reducing the transparency of the electrochromic glass; When the universal switch is turned on to connect the third contact (3) and the fourth contact (4) and the fifth contact (5) and the sixth contact (6), the voltage provided by the organic solar cell layer causes a reverse current to form in the electrochromic layer to cause the electrochromic layer to fade, thereby increasing the transparency of the electrochromic glass.
4. The electrochromic glass according to claim 1 or 2, wherein: The control circuit includes a voltage controller, which includes at least two relays and a single-chip microcomputer, each of the relays includes two contacts, the negative electrode of the electrochromic layer is electrically connected to the S1 and S4 contacts, and the positive electrode of the electrochromic layer is electrically connected to the S2 contact and the S3 contact; The threshold voltage of the single chip microcomputer is set, so that when the intensity of sunlight irradiating the electrochromic glass is high, the voltage provided by the organic solar cell layer is higher than the threshold voltage, and the single chip microcomputer controls the relay so that the anode of the organic solar cell layer is electrically connected to the S1 contact and the cathode is electrically connected to the S3 contact, thereby forming a forward current in the electrochromic layer to cause the electrochromic layer to be colored, thereby reducing the transparency of the electrochromic glass; when the intensity of sunlight irradiating the electrochromic glass is weak, the voltage provided by the organic solar cell layer is lower than the threshold voltage, and the single chip microcomputer controls the relay so that the anode of the organic solar cell layer is electrically connected to the S2 contact and the cathode is electrically connected to the S4 contact, thereby forming a reverse current in the electrochromic layer to cause the electrochromic layer to fade, thereby increasing the transparency of the electrochromic glass.
5. The electrochromic glass according to any one of claims 1 to 4, wherein: The organic solar cell layer includes a first transparent electrode layer, a hole transport layer, a photoelectric active layer, an electron transport layer, and a second transparent electrode layer arranged layer by layer, and the electrochromic layer includes a positive electrode, an electrochromic active layer, a negative electrode, and a glass layer arranged layer by layer; Preferably, the photoelectric active layer comprises an electron donor material and an electron acceptor material; Preferably, the electrochromic active layer comprises a peripheral frame and an internal cavity, and the internal cavity is provided with an electrochromic electrolyte; Preferably, the thickness of the photoelectric active layer is 40-120 nm, more preferably 60-90 nm; Preferably, the thickness of the electrochromic active layer is 0.01-5 mm, preferably 0.1-3 mm; Preferably, the first transparent electrode layer or the second transparent electrode layer and the positive electrode are two conductive surfaces of double-sided conductive glass; more preferably, the double-sided conductive glass is selected from one or more of double-sided indium tin oxide glass, double-sided indium zinc oxide glass and double-sided indium tungsten oxide glass.
6. The electrochromic glass according to claim 5, wherein: The electron donor material is one or more of the polymers containing the repeating structural units shown in formula (1): Wherein, the A group is selected from one of the structures shown in formula (1-a), formula (1-b) and formula (1-c): The electron acceptor material is one or more of the conjugated macromolecules shown in formula (2): Among them, the B group and the C group form a conjugated structure; The B group is selected from one of the structures shown in formula (2-a), formula (2-b) and formula (2-c): The C group is selected from 1 to 3 conjugated structures formed by formula (2-d) or is absent: The D group is selected from the group shown in formula (2-e) or is absent: The E group is selected from the group represented by formula (2-f): wherein each of R1, R2, R3, R4, R5, R6, R7, R8 and R9 is independently selected from H, C1-C30 alkyl, C6-C30 aryl and C1-C30 alkoxy or alkylthio; each of X1, X2, X3, X4, X5, X6, X7, X8 and X9 is independently selected from O, S and Se; each of Y1, Y2 and Y3 is independently selected from H and halogen atoms; And / or, the mass ratio of the electron donor material to the electron acceptor material is 1:1-10, preferably 1:1.5-5.
7. The electrochromic glass according to claim 6, wherein: Each of R1, R2, R3, R4, R5, R6, R7, R8 and R9 is independently selected from H, C1-C20 alkyl, C6-C20 aryl and C1-C20 alkoxy or alkylthio; each of X1, X2, X3, X4, X5, X6, X7, X8 and X9 is independently selected from O, S and Se; each of Y1, Y2 and Y3 is independently selected from H, F, Cl and Br; Preferably, each of R1, R2, R3, R4, R5, R6, R7, R8 and R9 is independently selected from H, C6-C12 alkyl, C6-C12 aryl and C6-C12 alkoxy or alkylthio; each of X1, X2, X3, X4, X5, X6, X7, X8 and X9 is independently selected from O, S and Se; each of Y1, Y2 and Y3 is independently selected from H, F and Cl; More preferably, each of R1, R2, R3, R4, R5, R6, R7, R8 and R9 is each independently selected from H, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, 2-ethylhexyl, 2-n-butyloctyl, n-hexyloxy, 2-ethylhexyloxy, n-nonyloxy, n-undecyloxy, n-hexylthio, n-nonylthio, n-undecylthio, p-n-propylphenyl and p-n-hexylphenyl.
8. The electrochromic glass according to claim 6 or 7, wherein: The polymer containing the repeating structural unit represented by formula (1) has a weight average molecular weight of 10,000-200,000 g / mol and a PDI of 1-5; And / or, the electron donor material is selected from one or more polymers containing repeating structural units represented by formula (1-1), formula (1-2) and formula (1-3): Preferably, the weight average molecular weight of the polymer containing the repeating structural unit represented by formula (1-1) is 10000-80000 g / mol, and the PDI is 1-3; the weight average molecular weight of the polymer containing the repeating structural unit represented by formula (1-2) is 20000-180000 g / mol, and the PDI is 1-3; the weight average molecular weight of the polymer containing the repeating structural unit represented by formula (1-3) is 10000-80000 g / mol, and the PDI is 1-3; Preferably, the electron donor material is selected from one or more polymers containing repeating structural units represented by formula (1-1-1), formula (1-2-1) and formula (1-3-1): Among them, -C4H9 is n-butyl, -C6H 13 It is n-hexyl.
9. The electrochromic glass according to any one of claims 6 to 8, wherein: The electron acceptor material is one or more of the structures shown in formula (2-1), formula (2-2), formula (2-3), formula (2-4) and formula (2-5): Preferably, the electron acceptor material is one or more of the structures shown in formula (2-1-1), formula (2-1-2), formula (2-1-3), formula (2-1-4) and formula (2-2-1): Among them, -C4H9 is n-butyl; -C6H 13 Is n-hexyl; -C9H 19 is n-nonyl; -C 11 H 23 It is n-undecyl.
10. A method for preparing the electrochromic glass according to any one of claims 1 to 9, comprising preparing the electrochromic layer and the organic solar cell layer and providing the control circuit to obtain the electrochromic glass.
11. The method according to claim 10, wherein: The method comprises: sequentially preparing the electron transport layer, the photoelectric active layer, the hole transport layer and the first transparent electrode layer on one conductive surface of the double-sided conductive glass to obtain the organic solar cell layer, or sequentially preparing the hole transport layer, the photoelectric active layer, the electron transport layer and the second transparent electrode layer on one conductive surface of the double-sided conductive glass to obtain the organic solar cell layer; and preparing the electrochromic active layer, the negative electrode and the glass layer on the other conductive surface of the double-sided conductive glass to obtain the electrochromic layer.
12. The method according to claim 10 or 11, wherein: The method comprises providing an electron transport material on one conductive surface of the double-sided conductive glass and performing a first thermal annealing treatment to form the electron transport layer, providing the electron donor material and the electron acceptor material on the electron transport layer and performing a second thermal annealing treatment to form the photoelectric active layer, providing a hole transport material on the photoelectric active layer to form the hole transport layer, providing a transparent electrode material on the hole transport layer and performing a thermal lamination treatment to form the first transparent electrode layer, thereby preparing the organic solar cell layer, or providing a hole transport material on one conductive surface of the double-sided conductive glass and performing a first thermal annealing treatment to form the hole transport layer, and providing a hole transport material on the hole transport layer. The electron donor material and the electron acceptor material are provided and subjected to a second thermal annealing treatment to form the photoelectric active layer, an electron transport material is provided on the photoelectric active layer to form the electron transport layer, a transparent electrode material is provided on the electron transport layer and subjected to a thermal lamination treatment to form the second transparent electrode layer, thereby obtaining the organic solar cell layer; the outer frame is provided on the other conductive surface of the double-sided conductive glass, a glass material sealed with a negative electrode material is provided on the outer frame to form the negative electrode and the glass layer thereon, and the electrochromic electrolyte is injected into the internal cavity surrounded by the outer frame to form the electrochromic active layer, thereby obtaining the electrochromic layer.
Citation Information
Patent Citations
Photochromic device
CN103777424A
Motor counter electromotive force measurement device
CN106997025A
Electrochromic device, preparing method and electrochromic glass
CN108646498A
Transparency adjustable intelligent toilet
CN109208942A
Information separation control system of subway station transparent display device
CN111276369A
Cited By
Self-adaptive color-changing semitransparent perovskite battery and preparation method and application thereof
CN121218769A